MSME Financial Accounting In West Java: Sustainability And Impact Factors - Heliani (Jurnal Akuntansi, 2023)
This study examines the relationship between financial accounting practices, including knowledge management, financial capability, technology adoption, financial performance, and the social impact of Micro, Small, and Medium Enterprises (MSMEs) in West Java, Indonesia. Quantitative research was adopted, and data were collected using structured survey questionnaires from 343 samples of MSME owners or financial managers in the regions. Data was analyzed using PLS-SEM with SmartPLS 4 software. The results confirm that financial accounting practices significantly affect MSMEs' financial performance and social impact. Knowledge management, financial capability, and technology adoption positively influenced financial performance and social impact. The study found that knowledge management is a significant factor in adopting technology. This study highlights the significant social impact of MSMEs on local communities and emphasizes the importance of sustainable financial accounting practices.